2018
DOI: 10.1016/j.ijedudev.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The politics of student mobility: Links between outbound student flows and the democratic development of post-Soviet Eurasia

Abstract: The study offers new empirical material to link student mobility and the levels of attained democracy in the former Soviet countries. Theoretically-informed analysis of crosssectional data shows that the former Soviet countries with higher proportions of students studying in Europe or the United States have achieved higher levels of democratic development. In contrast, countries with higher proportions of students studying in the most popular, authoritarian destination -Russia -have reached significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Thus, the contributions of higher education to development can be explained in very different ways. Although there are exceptions (Boni and Walker 2016;Chankseliani 2018), the existing academic writing on this topic is normally underpinned by essentialist assumptions of human capital and modernisation theories. A systematic analysis of literature has shown that the ways in which higher education can support development had been examined within five domains: earnings, productivity, technology transfer, capabilities, and institutions; most of these contributions were linked to the educational mission of higher education, rather than universitybased research or engagement (Oketch et al 2014).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Thus, the contributions of higher education to development can be explained in very different ways. Although there are exceptions (Boni and Walker 2016;Chankseliani 2018), the existing academic writing on this topic is normally underpinned by essentialist assumptions of human capital and modernisation theories. A systematic analysis of literature has shown that the ways in which higher education can support development had been examined within five domains: earnings, productivity, technology transfer, capabilities, and institutions; most of these contributions were linked to the educational mission of higher education, rather than universitybased research or engagement (Oketch et al 2014).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Following the dissolution of the Soviet Union, 15 countries chose divergent paths of economic, social, and political development (Chankseliani, 2018;Chankseliani & Silova, 2018a). Higher education and research policy discourses across post-Soviet countries emphasise global norms, global reputation, and global competitiveness (Chankseliani & Silova, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…This was certainly the case with Saakashvili, leader of the Rose Revolution, who received degrees in both the United States and France before returning to Georgia. More broadly, post-Soviet countries with the highest proportions of nationals studying in the United States or Europe experienced higher levels of democratic development (Chankseliani, 2018). Moreover, student mobility is seen as a tool to legitimize the quality of degrees earned in developing countries and positively influence higher education reforms (Rostiashvili, 2011).…”
Section: Private Higher Education In Georgiamentioning
confidence: 99%